Hubungan Motivasi dengan Produktivitas Karyawan di PT. Srikandi Inti Lestari - Yudi Daeng Polewangi; Budi Utomo (Universitas Medan Area, 2017)
Motivation is very important to be considered by the management if they want every employee make a positive contribution to achieve the corporate goals. Given the importance of motivation, the attention of management regarding to problem of employee motivation is to motivating employees in the company through a series of specific businesses in accordance to company policy, so the employees motivation will be maintained. This study to determine the relationship of motivation with employee productivity at PT. Srikandi Inti Lestari. The results describe employees of PT. Srikandi Inti Lestari has a high motivation and work productivity. Given the distribution of respondents' answers to the biggest motivation questions that agree 50%, strongly agree 20%, hesitate 18%, disagree 12% and strongly disagree 0%. Distribution of respondents' answers to the largest productivity question that is 46% agree, strongly agree 28%, hesitate 18%, disagree 8% and strongly disagree 0%. Based on this it is clear that the relationship between motivation and employee productivity in PT. Srikandi Inti Lestari influence each other with the value of 46% for productivity and 50% for motivation.